Ecological sustainability and personal behaviour: Relations demonstrated by the decision-making process of selecting a certain transportation mean - Reinhold Priewasser (European Regional Science Association (ERSA), 1998)
Up to now strategies and approaches of solving environmental problems facing the aim of sustainability have been primarily focussed on improving the ecological qualitiy of products, processes and technologies and on the discussion of structural changes in ecologically relevant sectors such as energy use, industry, tourism and traffic policy. Only few emphasis has been placed on the fact that the extent of environmental demands and ecological stresses is not only a consequence of certain factual or structural conditions but it is also essentially determined by varying human behavior patterns. Technologies and structures are not ecologically effective by themselves; their environmental relevance strongly depends on the persons way of acting within the prevailing systems. Accordingly it should become more evident in the political discussion and even in environmental research activities, that apart from technical and structural changes also changes of personal behavior patterns play an important role on the way to sustainability. Recognizing the importance of that perspective psychological and social theories about the generation of personal behavior als well as theoretical models of learning can offer useful indications concerning the intrapersonal and extrapersonal preconditions of environmentally orientated sustainable acting. With reference to the decision-making process of selecting a certain transportation mean the influences of rational and emotional factors and obstacles to ecologically sustainable personal acting should be examplary demonstrated. At the same time very effective points of departure for behavior changing can be identifed.
Keywords: 330